A 28-year-old male patient with asymptomatic and multi-drug-resistant HBV infection: a case report - Syed Ayaz Kazmi; Abdul Rauf; Muhammad Zahid Latif; Beenish Shahid; Sundus Khawaja; Zeeshan Anjum (Egyptian Liver Journal, 2024)
Abstract Chronic hepatitis B virus (HBV) infection poses a significant global health challenge, impacting millions of individuals and elevating the risk of morbidity and mortality. Antiviral therapies are the primary treatment for chronic HBV infection, but treatment resistance can occur, leading to poor clinical outcomes and an increased risk of liver complications. This case report presents the clinical trajectory of a 28-year-old male diagnosed with asymptomatic HBV infection in 2016 under the auspices of the Hepatitis Control Program, Government of Azad Jammu and Kashmir, Pakistan. Over 6 years, persistent HBsAg, HBV, and HBeAg were observed, with absent acute markers and co-infections. Initial HBV DNA viral load was 1 × 104 copies/mL in 2016, escalating despite entecavir and pegylated interferons therapy, indicating multi-drug resistance. Tenofovir therapy initially reduced viral load but later exacerbated it, reaching 1.86 × 106 copies/mL in 2022. Liver function abnormalities and lipid profile irregularities persisted. Urine examination consistently showed abnormalities. Pending HBV DNA sequencing results may offer insights into treatment resistance. This case underscores the need for an adaptive approach in managing chronic HBV infections within public health programs. Continuous monitoring, integration of virological and biochemical data, and a tailored treatment strategy are essential for optimizing outcomes in similar cases, stressing the importance of refining therapeutic approaches against chronic HBV infection.